2012
DOI: 10.4103/0976-237x.101100
|View full text |Cite
|
Sign up to set email alerts
|

Management of pulpal floor perforation and grade II Furcation involvement using mineral trioxide aggregate and platelet rich fibrin: A clinical report

Abstract: To report the management of an iatrogenic perforation of pulpal floor in the furcation of mandibular first molar, using Mineral Trioxide Aggregate (MTA) and platelet rich fibrin (PRF). Unpredictable endodontic root/pulp chamber floor perforations resulting in unacceptable high rate of clinical failure has now been a lesser threat with the advent of new technologies and biocompatible materials that utilize the applications of basic research along with tissue engineering concept in clinical practice. Present cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 16 publications
0
22
0
2
Order By: Relevance
“…Autologous PRF for the study was obtained from patient blood prior to surgery as suggested by Choukroun et al .,[ 4 ] by means of a table top centrifuge (REMI, Laboratories, India). [ 18 ] PRF acquired in the middle clot was cautiously collected by removing red blood cell clot using sterilized scissor [ Figure 2 ]. The PRF thus obtained was squeezed with sterilized and moist gauge piece to form PRF membrane.…”
Section: Methodsmentioning
confidence: 99%
“…Autologous PRF for the study was obtained from patient blood prior to surgery as suggested by Choukroun et al .,[ 4 ] by means of a table top centrifuge (REMI, Laboratories, India). [ 18 ] PRF acquired in the middle clot was cautiously collected by removing red blood cell clot using sterilized scissor [ Figure 2 ]. The PRF thus obtained was squeezed with sterilized and moist gauge piece to form PRF membrane.…”
Section: Methodsmentioning
confidence: 99%
“…The literature suggests that waiting for a minimum of 4 h under a moist cotton pellet (with the other surface exposed to moisture from dentinal tubules) will allow MTA to set adequately to achieve optimum flexural strength via two‐sided hydration . However, the recall period following perforation repair material placement has not been standardised by clinicians and has been reported to range from a few days to a week .…”
Section: Introductionmentioning
confidence: 99%
“…Endodontic treatment has been combined with the use of PRP, PRF and PRGF in 7 case reports and three controlled studies . All studies reported favorable and positive results with respect to periapical regeneration, pulp tissue regeneration, apical closure or regain of vitality.…”
Section: Resultsmentioning
confidence: 99%